The Impact of COVID-19 on Jobs in Korea: Does Contact-intensiveness Matter? - Sangmin Aum (KDI Journal of Economic Policy, 2022)
This paper studies how COVID-19 has affected the labor market in Korea through a general equilibrium model with multiple industries and occupations. In the model, workers are allocated to one of many occupations in an industry, and industrial or occupational shocks alter the employment structure. I calibrate the model with Korean data and identify industrial and occupational shocks, referred to here as COVID- 19 shocks, behind the employment dynamics in 2020 and 2021. I find that COVID-19 shocks are more severefor those with jobs with a higher risk of infection and in those that are more difficult to do from home. Interestingly, the relationship between COVID-19 shocks and infection risk weakened as the pandemic progressed, whereas the relationship between COVID-19 shocks and easiness of work-from-home strengthened. I interpret the results as meaning that the pandemic may direct future technological chang es to replace tasks that require contact-intensive steps, and I simulate the impact of such technological changes through the lens of the model. The results show that such technological changes will lower the demand for manual workers compared to the demands for other occupations. This contrasts with the earlier trend of job polarization, where manual workers continued to increase their employment share, with the share of routine workers secularly declining at the same time.
Keywords: E24; I14; J23; O33; 330; COVID-19; Contact Intensiveness; Job Polarization; Directed Technological Change